Design Description of a Tentacle Based Scanning System - Afolayan , M. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2017)
A design of a tentacle-based 3D object scanning device is presented in this work. The dimensions of the device were 15 ×15×20 cm and a maximum weight of model that can be placed on its platform is 500g.  The design requires that two red laser for distance measurement by triangulation be installed on the left and right side of a Charge Coupled Device (CCD) camera. The camera takes the reading as well. The 3D scanner body is made up of polymer matrix for rigidity and dimensional stability. The main mechanism for the scanner is a lead screw and a turntable both managed by National Electrical Manufacturers Association (NEMA) 17 stepper motors.